Perlindungan Hukum Terhadap Anak Dalam Proses Peradilan Sebagai Upaya Untuk Melindungi Hak Asasi Anak - Layyin Mahfiana (Justicia Islamica, 2009)
This study aims to examine the form of legal protection for children in the judicial process as part of an effort to guarantee and protect children's human rights in Indonesia. The method used is qualitative with a juridical-normative approach, through analysis of legislation, international conventions, and case studies of juvenile justice. The results show that the juvenile criminal justice system in Indonesia has improved, especially through the ratification of Law No. 11 of 2012 concerning the Juvenile Criminal Justice System. However, challenges in implementation such as a lack of trained human resources and a lack of supporting facilities are still major obstacles. This study emphasizes that effective legal protection requires collaboration between law enforcement, child protection agencies, and community participation to ensure a child-friendly judicial process that upholds children's rights.